Iron binary and ternary coatings with molybdenum and tungsten - Ved, M.; Sakhnenko, N. D.; Karakurkchi, A.; Yermolenko, I. Yu.; Yar-Mukhamedova, G. (Elsevier Inc., 2016)
Electrodeposition of Fe-Mo-W and Fe-Mo layers from a citrate solution containing iron(III) on steel and iron substrates is compared. The utilization of iron(III) compounds significantly improved the electrolyte stability eliminating side anodic redox reactions. The influence of concentration ratios and electrodeposition mode on quality, chemical composition, and functional properties of the alloys is determined. It has been found that alloys deposited in pulse mode have more uniform surface morphology and chemical composition and contain less impurities. Improvement in physical and mechanical properties as well as corrosion resistance of Fe-Mo and Fe-Mo-W deposits when compared with main alloy forming metals is driven by alloying components chemical passivity as well as by alloys amorphous structure. Indicated deposits can be considered promising materials in surface hardening technologies and repair of worn out items.

Покрытия сплавами Fe-Mo-W и Fe-Mo получены из цитратных электролитов на основе железа (III) на подложках из стали и чугуна. Использование солей железа(III) существенно повышает стабильность электролита за счет элиминирования побочных анодных реакций. Установлено влияние соотношения концентраций и режимов электроосаждения на качество, химический состав и функциональные свойства сплавов. Показано, что полученные в импульсном режиме сплавы характеризуются более равномерной поверхностью, распределением компонентов и содержат меньше примесей. Повышение физико-механических свойств и коррозионной стойкости покрытий Fe-Mo и Fe-Mo-W по сравнению со сплавообразующими металлами и подложкой обусловлено химической инертностью компонентов и аморфной структурой сплава. Полученные покрытия можно рассматривать как перспективные материалы для упрочнения поверхности и восстановления деталей.
Бинарные и тройные сплавы железа с молибденом и вольфрамом
Keywords: citrate electrolyte; physical-mechanical properties; electrodeposition; corrosion resistance; pulse electrolysis; электролит цитратный; свойства физико-механические; электроосаждение; стойкость коррозионная; электролиз импульсный